Phonological iconicity - Schmidtke, David; Conrad, Markus; Jacobs, Arthur M. (Frontiers in Psychology, 2014)
The arbitrariness of the linguistic sign is a fundamental assumption in modern linguistic theory. In recent years, however, a growing amount of research has investigated the nature of non-arbitrary relations between linguistic sounds and semantics. This review aims at illustrating the amount of findings obtained so far and to organize and evaluate different lines of research dedicated to the issue of phonological iconicity. In particular, we summarize findings on the processing of onomatopoetic expressions, ideophones, and phonaesthemes, relations between syntactic classes and phonology, as well as sound-shape and sound-affect correspondences at the level of phonemic contrasts. Many of these findings have been obtained across a range of different languages suggesting an internal relation between sublexical units and attributes as a potentially universal pattern.